JABATAN NOTARIS DI INDONESIA DALAM JERAT LIBERALISASI - Bachrudin Bachrudin (UNISSULA, 2015)
The function of Notary Public is as state’s representative in civil cases. The purposes of Notary Public’s figuration in a blueprint are for creating the regularity in law’s relationship. However, there are still liberalization’s phenomenon in practice position of Notary Public, such as “tariff war” and “certificate’s industrialization”. It is a form of “denial” of the respectability, dignity and prestige of Notary Public, which is worried, will pull down the respectability, dignity and prestige of Notary Public and also pull down the respectability and authority of the nationinh erently as the authority giver of Notary Public’s position. The state must give the special attention by applying the values of Pancasila as a unity and comprehensive in act’s regulations of Notary Public and practice position of Notary Public.